Five generations of applied linguistics: some framework issues - Albert Weideman (Acta Academica, 2024)
In recent years a number of discussions have sustained the debate on the def of applied linguistics, a debate which addresses both ends of the spectrum of applied linguistic work: the philosophical and the practical. This paper attempts to situate its response to such (re)considerations within an interpretative framework, considering the conception of the discipline as it has evolved over five generations. The argument of the paper is that the many and varied understandings of applied linguistic work during this period confirm the relativity of the discipline and prevent its practitioners from entertaining the illusion that, because they are involved in 'applied science', theit particular response to a language problem will provide a full and finite solution.